STRATEGI PENGEMBANGAN USAHA KOPI DI DAERAH TERTINGGAL MELALUI PENDEKATAN BISNIS INKLUSIF DI KABUPATEN SUMBA BARAT DAYA - Febtri Wijayanti; nFN Carolina (Analisis Kebijakan Pertanian, 2021)
The low bargaining power of small farmers put them into a disadvantage position. This is experienced by coffee farmers in Southwest Sumba District, as an underdeveloped area, which by their social economic limitation relies solely on middleman, while their coffee actually has higher value. This study examines these problems to find the best solution by utilizing local resources through an inclusive approach. Qualitative research was conducted through a case study in a disadvantaged village in Southwest Sumba District, which has intervened with appropriate technology to comprehensively handle coffee processing. The results of the study explain that the problem of coffee farmers stems from the obstacles and challenges that are typically faced by people in disadvantaged areas. Those roblems are: barriers access to inputs, market, financial, and socio-cultural factors; challenges in coordination; and inability to meet standardization consistently and to bear risks. These six problems become the basis for the design of the inclusive business concept that is proposed to be applied by utilizing existing physical and social infrastructure modalities in the village. The inclusive coffee business unit development strategy has the potential to assist coffee farmers in gaining access to inputs and optimizing output, but should be supported by cross-sectoral cooperation between the government institution, research and development institution, business, and the community. Efforts to develop this business model need to be carried out sustainably along with empowering farmers and increasing awareness of the stakehoder to work together in an integrated manner.